Research handbook on interdisciplinary approaches to law and religion - Sandberg, Russell; Doe, Norman; Kane, Bronach; Roberts, Caroline; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2019)
"Law and religion, as a subdiscipline of law, has gained increasing attention in recent years. However, the complex relationship between law and religion cannot be fully understood with reference to legal research alone. This Research Handbook includes provocative chapters from experts on a range of concepts, perspectives and theories, drawing on a variety of disciplines, which can be used to further law and religion scholarship. Featuring chapters written by authors from a diverse range of backgrounds, the Handbook focuses on five main perspectives on law and religion: historical, philosophical, sociological, theological and comparative. Each chapter provides a new way of looking at law and religion which can complement and enhance a doctrinal legal understanding of the topic. Crucially, this Handbook also highlights the importance of recognising doctrinal legal study as an approach in itself, which will shape research questions and outputs accordingly. Providing an engaging and thoughtful introduction to the range of interdisciplinary approaches that can be taken to law and religion, this Handbook will be of interest to scholars in law and religion, theologians, sociologists, legal historians and political scientists. It will provide a rich foundation for future interdisciplinary research in this important area of study"--
Preface -- Introduction -- 1: Snakepits & sandpits / Russell Sandberg -- Part I: Historical approaches -- 2: Ecclesiastical court records for social and cultural history / Bronach C Kane -- 3: Trial by ordeal: An interdisciplinary approach yields fresh insights / Lindsey Bell -- 4: 'moved and seduced by the instigation of the devil': witchcraft and the law, 1450-1700 / Jan Machielson -- 5: Secularisation and law in modern societies / Callum G Brown -- Part II: Philosophical approaches -- 6: Philosophy, law, and religion / Daniel Whistler and Daniel J Hill -- 7: Law, religion, and public reason / Paul Billingham and Jonathan Chaplin -- 8: Multicultural political theory / Simon Thompson and Tariq Modood -- 9: Charles taylor on recognition, inclusive secularism, and religion / Camil Ungureanu and Paolo Monti -- 10. 'Gods would be needed ...': Derrida on law and religion / Peter Fitzpatrick -- Part III: Sociological approaches ---11: Interpretive issues in researching law and religion / Max Travers and Doug Ezzy -- 12: The lure of luhmann: a systems theory of law and religion / Russell Sandberg -- 13: Social anthropology / Méadhbh McIvor -- 14: religion or belief, equality and human rights law and the media / David Perfect and Simon Perfect -- Part IV: Theological approaches -- 15: Biblical law / Jonathan Burnside -- 16: Political theology and legal theory / Joshua Neoh -- 17: Feminism meets law and religion: commonalities and critiques / Marie A Failinger -- Part V: Comparative approaches -- 18: A comparative method for the study of law and religion: Is this a defensible methodology? / Brigitte Clark -- 19: Monotheism and the death penalty: Towards a homogenous exegesis for abolition / Jon Yorke and Amna Nazir -- 20: The Turkish constitutional court rulings on the headscarf: the construction of villains and victims / Laçin İdil Öztığ ---21: Diversity in death: a case study of a Muslim cemetery project in Quebec / Dia Dabby and Lori G Beaman -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: právo a náboženství; religion and law; e-knihy online; e-books online